An Intelligent Superwetting PVDF Membrane Showing Switchable Transport Performance for Oil/Water Separation. (12th February 2014) - Tao, Mimi; Xue, Lixin; Liu, Fu; Jiang, Lei
<x xml:space="preserve">Abstract</x> A superamphiphilic poly(vinylidene fluoride) (PVDF) membrane with superoleophobicity under water and superhydrophobicity under oil is successfully prepared. Due to the switchable transport performance, the membrane is applicable to the separation of various oil‐in‐water and water‐in‐oil emulsions with a droplet size greater than 20 nm, and shows superior permeability and antifouling properties, as well as a high separation efficiency. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>